PENGARUH TIPE NHT TERHADAP HASIL BELAJAR KONSEP MAGNET SISWA KELAS V SEKOLAH DASAR - Fajar Satrio Dermawan; Hery Kresnadi; Endang Uliyanti (Universitas Tanjungpura, 2019)
AbstractThis study aimed to analyze the effect of the application of number head together on the results of learning the concept of magnetism in learning natural sciences of class V students of Pontianak City 24 Elementary School. The method used is the experimental method, while the form of research used is quasi experimental design with nonequivalent control group design. The population and sample in this study were all fifth grade students of Pontianak City 24 Elementary School. The data collection tool used was a multiple choice test with 45 questions. Based on data analysis, the average post-test results of the experimental class were 65,05 while the average post-test results of the control class were 59,25. The results of the t test are obtained tcount of 1,697 and t table α = 5% (with dk = 32 + 12 - 2 = 61) of 1,671, which means tcount (1,697)> t table (1,671), then the alternative hypothesis (Ha) is accepted. It can be concluded that there is influence the application of number head together on results of learning the concept of magnetism in learning natural sciences in class V of Pontianak City 24 State Elementary School. From the results of the calculation of the effect size (ES) ES obtained is 0,3242 (medium criteria). This means that the application of number head together have a good influence on the results of learning the concept of magnetism in learning natural sciences of class V students of Pontianak City 24 Elementary School Keywords: Learning Outcomes, Number Head Together, The Concept Of Magnetisme